BMC converter bottom thermal-state repairing material and repairing method
Through the combination of magnesium-calcium iron sand, magnesium sand powder, magnesium sand powder and nano-silicon sol repair materials, the problem of poor sintering of the converter bottom repair materials is solved, rapid sintering and efficient corrosion resistance and oxidation resistance are achieved, and the service life of the converter is extended And improve turnover efficiency.
Patent Information
- Application Number
- CN202310739933.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-24
AI Technical Summary
In the prior art, the sintering property of the converter bottom repair material has poor sintering, resulting in low repair efficiency, short life, and environmental protection problems, which cannot effectively prevent slag penetration and antioxidation, affecting the functions of the converter bottom and blowing elements.
Using repair materials composed of magnesium-calcium iron sand, magnesium sand powder, magnesium sand powder and nano-silicon sol, through solid phase reaction and sintering under high temperature conditions, the refractory phase MgO-C3S-C2S and high melting point phase are formed quickly. The working layer improves corrosion resistance and oxidation resistance.
It shortens the repair time and extends the service life of the converter. After a single repair, it can continuously use 25 to 30 furnaces, which improves turnover efficiency and is environmentally friendly, does not produce harmful flue gas, and maintains good breathability and blowing component functions.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of steelmaking, and in particular relates to a BMC converter bottom hot repair material and a repair method. Background Art
[0002] Currently, more stringent requirements are being put forward for the steel industry. To change the current technological status quo of the long blast furnace-converter process with large carbon emissions, the key lies in increasing the scrap steel ratio in the converter process and increasing the use of scrap steel, which is an effective way to reduce CO2 emissions.
[0003] In order to increase the scrap steel ratio of the converter, a converter bottom blowing powder steelmaking process using a CO2-O2 mixed gas as the powder carrier gas can be developed. New technologies developed include converter bottom blowing lime powder, bottom blowing carbon powder mode, and breakthrough technologies including bottom blowing oxygen, bottom blowing natural gas, top and bottom composite oxygen blowing, forming a new BMC converter steelmaking technology.
[0004] However, the new BMC converter steelmaking technology is a great test for the life and function of the converter bottom and the blowing elements. The converter bottom is an important part of the converter body. It is always in a high temperature and heavy-loaded state during the converter smelting process. The BMC converter steelmaking technology makes the w(O) in the molten steel higher, causing more serious oxidation and erosion of the converter bottom, resulting in more frequent and long maintenance of the bottom. Some even have to replace the bottom several times during the converter overhaul service, resulting in low converter operation efficiency and high production costs.
[0005] In order to maintain the bottom of the converter and achieve good metallurgical effects, technicians have developed many methods to maintain the bottom of the converter, protect the refractory materials of the bottom working lining and the blowing elements. In the prior art, some add lime after the slag is poured out after the slag splashes, so that the lime sticks to the bottom of the converter to reduce the erosion of the bottom of the converter. Some use large fabrics to repair the bottom of the converter, but the repair process takes 40 minutes, and the effect is not ideal, and the erosion is fast. Some use large fabrics and furnace bricks (C12% magnesia carbon bricks) to repair the bottom of the converter. The repair process takes 100 minutes, and the service life can be more than 10 furnaces, but the repair and baking curing time is long, which is insufficient in time efficiency.
[0006] Others use pig iron block slag repair technology. The repair process only takes 10 minutes. By adding pig iron blocks, the slag is condensed and adhered to the furnace, so that the patched parts are repeatedly slag-attached during the furnace shaking process to achieve the purpose of furnace protection. This method has low cost and fast sintering of repair materials. However, since the maintenance material is composed of converter slag and iron blocks, the service life of a single repair furnace bottom is only one furnace. After smelting one furnace, the modified material will melt away, so the furnace bottom needs to be repaired after each smelting, which significantly reduces the process finishing efficiency. Generally speaking, it is not cost-effective.
[0007] Chinese patent CN103290167A discloses "a method for improving the service life of the bottom of a top and bottom composite blowing converter" and introduces a furnace repair material: MgO: 75-85%, C: 7-14%, CaO: 1-3%, SiO2: 1-2%, and a binder of 2-10%. After adding the furnace repair material into the furnace, it is naturally sintered for 40-70 minutes at the furnace temperature, and then sintered for 60-120 minutes at 700-1200 degrees. It can be put into smelting, effectively improving the service life of the converter bottom bricks and the bottom air bricks. The patent introduces that the furnace repair material binder is one or more of phenolic resin and asphalt. Because it contains carbon, the material is not resistant to oxidation. If an organic binder is used, there are environmental problems during the sintering process. The sintering time is relatively long when the furnace bottom is repaired using the patented furnace repair material.
[0008] Chinese patent CN107557518A discloses "a method for maintaining the bottom of a dephosphorization converter", in which liquid decarbonization slag is added to the dephosphorization converter after steelmaking, and then cold solidified pellets are added to implement slag splashing and furnace protection operations. The decarbonization slag contains CaO: 32.14-47.78%, SiO2: 6.72-14.96%, MgO: 7.14-18.55%, and FeO: 17.60-35.27%. The advantages of this method are solid waste resource utilization, low cost, and fast repair. The disadvantages are that the furnace protection material has poor corrosion resistance and high temperature resistance, and has a short lifespan. It is necessary to carry out furnace maintenance for each furnace, and a large amount of slag is brought in, requiring about 15 tons of material each time. Although the slag has good solubility, it will cause blockage to the converter bottom blowing element.
[0009] Chinese patent CN107012289A discloses "a method for repairing the bottom of a converter". After the molten steel in the converter is discharged, the slag is left in the converter, and then a furnace repair material containing MgO ≥ 65wt% and C ≥ 2wt% is added. The slag is directly splashed for more than 3 minutes using a slag splashing gun. After the slag splashing is completed, the converter is stationary at zero position for more than 30 minutes. This invention can improve the corrosion resistance of the furnace bottom and the ball-notch part, and achieve the synchronous longevity of the converter lining. This technology also utilizes the molten slag solid waste resources, but the operation still requires sintering for 30 minutes. The molten slag is not resistant to corrosion during the converter smelting process, and the furnace bottom still needs to be repaired for the life of the furnace bottom.
[0010] Chinese patent CN108191405A discloses "a new type of converter bottom repair material", which includes: 55-65% recycled magnesium particles; 18-23% magnesia powder; 5-10% recarburizer; 10-15% binder, which is a mixed powder composed of resin powder, glucose and sodium silicate; 0.1-0.5% flow aid containing paraffin or industrial naphthalene; 0.01-0.06% composite antioxidant of metal powder and boride; 0.1-1.5% sintering agent, which is one or more of bentonite, silica powder, clay and slaked lime. However, the repair material in this patent uses resin as a binder, which is not sinterable and environmentally friendly.
[0011] In addition to using slag and pig iron blocks to maintain the furnace bottom, the existing hot repair and maintenance materials for converters are mainly magnesium and magnesium-calcium. The main raw materials are usually sintered magnesia, fused magnesia, dolomite sand or synthetic magnesium-calcium sand, etc. The sintering agent and binder are usually resin, asphalt, silicate, phosphate, etc. The cost of these technologies and raw materials is high. Although they have their own advantages and disadvantages in terms of corrosion resistance, air permeability and other properties, the common disadvantage is that the sintering property of the material is not good, which affects the repair time. The efficiency of converter bottom repair using existing repair materials or methods is low, the life of the furnace bottom after repair is short, or the furnace bottom blowing function is not good. At present, no furnace bottom repair materials and converter bottom maintenance methods with good comprehensive effects have been found.
[0012] For BMC converter, the converter bottom is the core part of the converter composite injection process, and the bottom injection element is the key to the advanced steelmaking technology of BMC converter. Better requirements are put forward for the repair material, which not only requires the repair material to sinter quickly and form a solid working layer, but also has excellent anti-corrosion and anti-oxidation properties, and can prevent slag penetration to the maximum extent, protect the converter bottom working lining and injection elements, and maintain a moderate porosity, so as not to block and affect the function of the bottom injection element. Summary of the invention
[0013] The purpose of the present invention is to provide a BMC converter bottom hot repair material and a repair method. The converter repaired with the repair material has higher strength, can resist corrosion and oxidation, and improves the service life of the converter after a single repair; at the same time, it ensures that the converter bottom and the blowing elements after the repair have good air permeability and are not blocked, so that the bottom blowing is unobstructed throughout the service life of the furnace, and the life of the bottom blowing gas supply element is synchronized with the furnace age; moreover, the cost of the repair material is low, the repair process time is short, and it is green and environmentally friendly.
[0014] In order to achieve the above object, the present invention provides the following technical solutions:
[0015] A hot repair material for a BMC converter bottom, the weight percentage of which is as follows: 36-54% of magnesia-calcium-iron sand, 25-35% of magnesia powder, 3-9% of magnesia micropowder, and 16-20% of nano-silica sol; the magnesia powder contains MgO content greater than 97wt%, SiO2 content less than 0.5wt%, and the particle size is ≤1mm; the magnesia micropowder contains MgO content greater than 95wt%, SiO2 content less than 0.8wt%, and the particle size is ≤10μm.
[0016] Preferably, the MgO content in the magnesium-calcium-iron sand is ≥80wt%, the CaO content is ≥8wt%, and the Fe2O3 content is ≥5wt%.
[0017] Preferably, the SiO2 content in the nano-silica sol is ≥30wt%, and the specific gravity is 1.10-1.20g / cm 3 .
[0018] The magnesium calcium iron sand (MgO-CaO-Fe2O3) used in the present invention can be sintered magnesium calcium iron sand or fused magnesium calcium iron sand. In the magnesium calcium iron sand, the main crystal phase is periclase (MgO), the secondary crystal phase is dicalcium ferrite (C2F, i.e. 2CaO.Fe2O3), and a small amount of tetracalcium aluminoferrite (4CaO·Al2O3·Fe2O3), magnesium ferrite (MgO·Fe2O3) and calcium (CaO), etc.
[0019] The repair material of the present invention uses magnesium calcium iron sand (MgO-CaO-Fe2O3) as the main raw material. Magnesium calcium iron sand has the characteristics of high corrosion resistance, easy sintering and not easy hydration under high temperature conditions; and the thermodynamic stability of the cementing phase dicalcium ferrite (C2F) in magnesium calcium iron sand is mainly due to P O2 Decision, P O2 When P is higher, C2F melts uniformly at 1400℃; O2 When the temperature is low, C2F decomposes and melts at 1380℃ and reacts with MgO to form a high melting point phase. Therefore, magnesium calcium iron sand is used to repair the bottom of the converter. The repaired surface formed after the repair is resistant to high temperature corrosion under normal operating conditions of the converter, and can also have a good sintering to form a ceramic bond, making the repaired surface more solid and able to withstand mechanical impact when loading scrap steel.
[0020] In order to further enhance the anti-corrosion performance of the repair material, 25-35% of magnesia fine powder and 3-9% of magnesia micro powder are added to the repair material of the present invention, wherein the MgO content of the magnesia fine powder is >97wt%, the SiO2 content is <0.5wt%, and the particle size is ≤1mm, and the MgO content of the magnesia micro powder is >95%, the SiO2 content is <0.8%, and the particle size is <10um. The surface activity of the magnesia micro powder promotes the solid phase sintering of the material, so that the repair body obtains excellent high temperature performance, and at the same time, a good high temperature structural strength is constructed to ensure the minimum penetration of molten slag iron, which can further improve the service life of the repaired converter.
[0021] The present invention adds nano-silica sol as a binder, a flow agent and a sintering agent, wherein the nano-silica sol is rich in nano-scale SiO2, the SiO2 content in the nano-silica sol is ≥30wt%, and the specific gravity is 1.10-1.20g / cm 3 By controlling the particle size of the raw materials added and combining the addition of nano-silica sol, the obtained maintenance material is ensured to have good fluidity and can be well laid on the bottom of the converter.
[0022] When the repair material of the present invention is at low or medium temperature, the nano-silica sol takes effect, quickly makes the material strong, solidifies and adheres to the furnace lining, so that the furnace bottom can resist scouring and charge impact. When the temperature reaches above 1250°C, the C2F in the repair material can be dissolved in the periclase, and at the same time, a small amount of periclase will be dissolved in the C2F to form a solid solution. This mutual dissolution process is due to the activation of the MgO lattice by C2F. As the temperature rises, the reaction becomes more intense, and solid-phase reaction sintering with the participation of the liquid phase is quickly achieved. The C2F in the repair material decomposes and melts in the MgO phase to form the RO phase, and CaO forms a calcium-rich liquid phase or precipitates CaO crystals or reacts with SiO2 to form C2S, and MgO+C2F is transformed into RO+SiL, and the sintering process is quickly completed, and the sintering time is shortened to less than 12 minutes, which greatly shortens the converter repair time and improves the converter turnover efficiency.
[0023] The main components of the repair material of the present invention are MgO, CaO, SiO2 and FeOn, among which Fe 2+ Most of them are dissolved in periclase to form RO phase. The refractory property of the material increases with the increase of the MgO / FeO ratio contained in the material. The CaO / SiO2 ratio in the repair material gradually increases until it reaches the maximum value through the infiltration of converter slag. At the same time, the silicate phase in the repair material is also transformed into C3S+C2S, which together with the periclase in the repair material forms a new refractory phase: MgO-C3S-C2S.
[0024] Since there are a lot of MgO and 2CaO·Fe2O3 (C2F) in the repair material, they will be reduced and decomposed at the interface between the molten steel and the furnace bottom, and finally CaO and (Mg·Fe)O will be obtained, which are high melting point phases. The specific chemical reactions are as follows:
[0025] 2CaO·Fe2O3 = 4CaO+ 4FeO+ O2 (1)
[0026] FeO diffuses into the periclase lattice to form a solid solution:
[0027] xMgO+ 4FeO =(x+4) (Mg·Fe) O (2)
[0028] The size of periclase crystals increases due to the absorption of FeO, and the degree of direct bonding between them increases, which increases the strength and improves the refractory properties of the molten pool mixture.
[0029] The remaining slag in the converter corrodes the repair material, mainly reacting with SiO2 and FeO in the following ways:
[0030] 2CaO+ SiO2=2CaO·SiO2 (3)
[0031] FeO+ (Mg Fe)O = (Mg·Fe)O (4)
[0032] The result of reaction (3) is the formation of high melting point phase 2CaO·SiO2, which exists between the main crystal phase periclase solid solution, preventing the slag from further infiltration. Reaction (4) only relatively increases the Fe content in the periclase solid solution. 2+ The concentration promotes crystal growth and makes the repaired furnace bottom denser.
[0033] Since reactions (3) and (4) are both carried out on the repaired surface, the reaction products form a high melting point phase, which increases the service life of the repaired converter.
[0034] Moreover, the repair material of the present invention does not need to be sintered by adding inorganic or organic low-melting-point substances, and generates refractory phases MgO-C3S-C2S and high-melting-point phases 2CaO·SiO2, CaO and (Mg·Fe)O during the repair process, thereby extending the service life of the converter after a single repair. At the same time, it is quickly sintered at the converter temperature to form a solid working layer, giving the converter bottom good high-temperature strength, excellent anti-corrosion performance, and greater resistance to scouring and charge impact. After a single repair of the converter, the converter can be used continuously for 25 to 30 furnaces, and has a very high service life.
[0035] The method for repairing a converter bottom using the BMC converter bottom hot repair material comprises the following steps:
[0036] 1) Preparation of repair materials
[0037] Prepare raw materials of magnesium calcium iron sand, magnesium sand powder, magnesium sand micropowder and nano silica sol according to the above ingredients, first mix magnesium calcium iron sand, magnesium sand powder and magnesium sand micropowder evenly, then add nano silica sol and stir evenly to obtain repair material for use;
[0038] 2) Adding materials
[0039] After the converter is slag-tapped, the obtained repair material is added into the converter furnace, and the repair material is added according to the size of the furnace bottom to be repaired;
[0040] 3) Sintering
[0041] After the repair material is added into the furnace, the furnace is shaken to spread the repair material on the furnace bottom, and sintered for 8 to 12 minutes to complete the furnace bottom repair and maintenance.
[0042] Preferably, the time interval from the preparation of the obtained repair material to its use in the converter is less than 30 minutes.
[0043] Preferably, the amount of the repair material added is 0.5-3 t.
[0044] The repair material obtained after uniformly mixing the raw material components according to the present invention cannot stay for a long time. The time interval from preparation completion to being put into the converter is less than 30 minutes to avoid being added into the converter after solidification and not being able to spread well on the bottom of the converter.
[0045] When the repair material of the present invention is used to maintain the converter bottom, the sintering time only needs 8 to 12 minutes, which greatly shortens the sintering time compared with the time required for traditional converter repairs.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] The repair material of the present invention generates the refractory phase MgO-C3S-C2S, as well as the high melting point phases 2CaO·SiO2, CaO and (Mg·Fe)O during the maintenance process, and simultaneously rapidly sintered at the converter temperature to form a solid working layer, giving the converter bottom good high temperature strength, excellent corrosion resistance, more erosion resistance, and better resistance to charge impact, extending the service life of the converter after a single repair. After a single repair of the converter, the converter can be used continuously for 25 to 30 furnaces, while the service life of the converter after maintenance by the existing repair method is only about 10 furnaces at most. Moreover, on the basis of shortening the converter maintenance time, the present invention also ensures the service life of the converter after a single maintenance, and significantly improves the converter turnover efficiency.
[0048] The repair material of the present invention is prepared by mixing the proportions of magnesium calcium iron sand, magnesium sand powder, magnesium sand powder, and nano silica sol. Due to the mutual dissolution of C2F in the repair material and periclase, solid phase reaction sintering with liquid phase participation is quickly achieved, shortening the sintering time to less than 12 minutes; while the traditional converter repair sintering time takes at least 30 minutes. Therefore, the repair material of the present invention is used to maintain the converter bottom, which greatly shortens the converter repair time and improves the converter turnover efficiency.
[0049] Compared with existing repair materials, the repair material of the present invention does not need to rely on the addition of inorganic or organic low-melting-point substances to achieve sintering, and avoids the addition of carbon-containing organic binders, such as asphalt, tar, resin or alcohol, etc., and is more environmentally friendly. It does not emit yellow smoke, black smoke or irritating gas during use.
[0050] The raw materials used in the present invention are all carbon-free, so they have excellent antioxidant properties and do not need to add high-cost antioxidants, ensuring that the repaired converter bottom working lining and blowing elements have good air permeability and will not be blocked to affect the function of the bottom blowing elements. DETAILED DESCRIPTION
[0051] The present invention is further described below in conjunction with specific embodiments.
[0052] The ingredients of the maintenance materials of the embodiments of the present invention and the comparative examples are shown in Table 1.
[0053] The converter was repaired using the repair material composition described in the embodiment of the present invention and the comparative example, and the required sintering time and the smoke generated during the sintering process were recorded. The specific results are shown in Table 2.
[0054] The bulk density, porosity and compressive strength of the repaired converter bottom were measured after calcining at 1500°C for 3 hours. See Table 2 for specific results.
[0055] The repaired converter was used continuously under the same conditions, and the number of times the converter could be used continuously was recorded. The specific results are shown in Table 2.
[0056] It can be seen from Table 2 that when the repair material of the present invention is used to repair the converter, the sintering time required during the maintenance process is within 12 minutes, and no black smoke is generated during the sintering process; and the converter bottom has a high volume density and high compressive strength, and a good porosity is obtained. The air permeability is not affected by the porosity being too low, and the air permeability is not deteriorated due to slag blockage during use due to the porosity being too high. The converter is ensured to have good air permeability and the function of the converter bottom blowing element is not affected.
[0057] After a single repair of the converter, it can be used continuously for 25 to 30 furnaces. In comparison, the best usage number is only a dozen furnaces.
[0058] The repair material of the present invention has excellent comprehensive performance, can ensure the bottom blowing and stirring effect in the smelting process and prolong the life of the converter bottom, and meet the high-efficiency and low-carbon production needs of the steel plant.
[0059] The repair materials used in Comparative Examples 1 and 2 are significantly different from those of the present invention, and the sintering time required is much longer than that of the present invention. Black smoke is emitted during the sintering process, which is not environmentally friendly. The compressive strength, service life and air permeability of the converter after repair are not as good as those of the present invention.
[0060] Comparative Example 3 directly uses slag to repair the converter. Although the sintering time is similar to that of the present invention, the compressive strength and air permeability are not as good as those of the present invention. The most important thing is that the corrosion resistance is poor, and the service life is only one furnace, which is far lower than that of the present invention.
[0061]
[0062]
Claims
1. A hot repair material for a BMC converter bottom, comprising the following components by weight: 36-54% magnesia-calcium-iron sand, 25-35% magnesia powder, 3-9% magnesia powder, and 16-20% nano-silica sol; the particle size of the magnesia-calcium-iron sand is ≤4 mm; the MgO content in the magnesia powder is >97wt%, the SiO2 content is <0.5wt%, and the particle size is ≤1 mm; the MgO content in the magnesia powder is >95wt%, the SiO2 content is <0.8wt%, and the particle size is ≤10 μm.
2. The BMC converter bottom hot repair material according to claim 1 is characterized in that: The magnesium calcium iron sand contains MgO content ≥80wt%, CaO content ≥8wt%, and Fe2O3 content ≥5wt%.
3. The BMC converter bottom hot repair material according to claim 1, characterized in that: The SiO2 content of the nano-silica sol is ≥30wt%, and the specific gravity is 1.10-1.20g / cm 3 .
4. A method for repairing a converter bottom using the BMC converter bottom hot repair material according to claim 1, 2 or 3, characterized in that: The following steps are involved: 1) Preparation of repair materials Prepare raw materials according to the ingredients of claim 1, 2 or 3, namely, magnesium calcium iron sand, magnesium sand powder, magnesium sand micropowder and nano silica sol, first mix the magnesium calcium iron sand, magnesium sand powder and magnesium sand micropowder evenly, then add nano silica sol and stir evenly to obtain a repair material for use; 2) Adding materials After the converter is slag-tapped, the obtained repair material is added into the converter furnace, and the repair material is added according to the size of the furnace bottom to be repaired; 3) Sintering After the repair material is added into the furnace, the furnace is shaken to spread the repair material on the furnace bottom, and sintered for 8 to 12 minutes to complete the furnace bottom repair and maintenance.
5. The method for repairing a furnace bottom according to claim 4, characterized in that: In step 1), the time interval from the preparation of the obtained repair material to its use in the converter is less than 30 minutes.
6. The method for repairing a furnace bottom according to claim 4, characterized in that: In step 2), the amount of the repair material added is 0.5 to 3 t.
Citation Information
Patent Citations
Conductive refractory material for hot repair of bottom of electric furnace
CN115259865A
